Peculiarities of using force efforts as method of getting better of physical development of boys of 5-6 classes in the process of faculties of sport gymnastics. - Proskurov E.M (Kharkov National Pedagogical University, 2011)
Any impellent activity is connected with display force efforts directly participating in movement, from that on how many these efforts are correct, depends its result. The special value it has at performance of impellent actions on gymnastic shells. Clause considers a problem of use of the most effective technique promoting to development of general and special force abilities, for the module "gymnastics" from the school program of physical education. As comparison act: a traditional technique of development of force qualities and technique including a principle of structural similarity specific requirements.